2022
DOI: 10.3390/ijerph19116507
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition in Preterm and Full-Term School-Age Children

Abstract: Children born preterm (<37 weeks’ gestation) show a specific vulnerability for socio-emotional difficulties, which may lead to an increased likelihood of developing behavioral and psychiatric problems in adolescence and adulthood. The accurate decoding of emotional signals from faces represents a fundamental prerequisite for early social interactions, allowing children to derive information about others’ feelings and intentions. The present study aims to explore possible differences between preterm and full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 88 publications
0
8
1
Order By: Relevance
“…Results showed that both EPT and VPT subgroups had poorer performance in perception of biological motion associated with dorsal stream information processing, but the difficulties may have varied in functions associated with the ventral stream route such as static shape and emotion perception. The results for perception of emotion partly contradicted earlier studies indicating that children born very preterm had difficulties in interpreting facial expressions, since poorer results on both the static shape perception test and the perception of emotion test were associated with lower gestational age in the EPT group 7 . Timing can be crucial for social functioning and scores from the standardised perception of emotion test do not incorporate the time to match emotions.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…Results showed that both EPT and VPT subgroups had poorer performance in perception of biological motion associated with dorsal stream information processing, but the difficulties may have varied in functions associated with the ventral stream route such as static shape and emotion perception. The results for perception of emotion partly contradicted earlier studies indicating that children born very preterm had difficulties in interpreting facial expressions, since poorer results on both the static shape perception test and the perception of emotion test were associated with lower gestational age in the EPT group 7 . Timing can be crucial for social functioning and scores from the standardised perception of emotion test do not incorporate the time to match emotions.…”
Section: Discussioncontrasting
confidence: 78%
“…Children born preterm with a gestational age below 32 weeks have an increased risk of developing white and grey matter brain injury associated with later perceptual problems and social difficulties 1–4 . Deficits in visual perception include poorer perception of shapes and spatial relations between objects, difficulties with facial recognition and decreased ability to perceive moving patterns 5–7 . The neural processing of visual information includes two pathways, the ventral stream and the dorsal stream 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations